Sizing of power electronics EMC filters using design by optimization methodology - Schanen, J.L.; Baraston, A.; Delhommais, M.; Zanchetta, P.; Boroyevich, D. (2016)
This paper proposes a synthesis of EMC filter design method for power electronics converters. It starts with the description of the legacy approach, using the usual Common Mode / Differential Mode decomposition, and underlines the need of symmetry and the associated limits. Then an illustration of a design by optimization process is provided in the case of a simple switching cell. Finally, a full system composed of a PFC rectifier is provided, using EMC filters on both AC and DC sides. This example requires a design by optimization, since the two filters exhibit strong interactions.